Path dependence of the quark nonlocal condensate within the instanton model - Trevisan, L. A. [UNESP]; Dorokhov, A. E.; Tomio, Lauro [UNESP] (Sociedade Brasileira de Física, 2004)
Within the instanton liquid model, we study the dependence of the gauge invariant two-point quark correlator on the path used to perform the color parallel transport between two points in the Euclidean space.